Ebola Virus Transmission Caused by Persistently Infected Survivors of the 2014–2016 Outbreak in West Africa. (18th June 2018) - Subissi, Lorenzo; Keita, Mory; Mesfin, Samuel; Rezza, Giovanni; Diallo, Boubacar; Van Gucht, Steven; Musa, Emmanuel Onuche; Yoti, Zabulon; Keita, Sakoba; Djingarey, Mamoudou Harouna; Diallo, Amadou Bailo; Fall, Ibrahima Soce
Abstract: The 2014–2016 Ebola virus (EBOV) disease outbreak affected over 29000 people and left behind the biggest cohort (over 17000 individuals) of Ebola survivors in history. Although the persistence of EBOV in body fluids of survivors was reported before the recent outbreak, new evidence revealed that the virus can be detected up to 18 months in the semen, which represents the biggest risk of Ebola resurgence in affected communities. In this study, we review the knowledge on the Ebola flare-ups that occurred after the peak of the 2014–2016 Ebola epidemic in West Africa.